Lattice Boltzmann simulation of fluid flow and heat transfer in a micro channel with heat sources located on the walls. (December 2021) - Javaherdeh, Kourosh; Karimi, Habib; Azarbarzin, Touraj
Abstract: This study investigated a numerical study of fluid flow and heat transfer in micro channel with four heat sources that located on upper and lower walls. Four heat sources are located in the upper and lower walls symmetrically respect to centerline. Lattice Boltzmann method is used to solve related equations of flow and temperature of fluids, this method is included two steps such as collision and streaming steps. Reynolds number is varied from 0.1 to 10 and Knudsen number is changed from 0 to 0.1 for air. The slip velocity and temperature jump boundary condition are used for micro channel simulation with Knudsen numbers related to slip velocity flow. Bounce-back boundary conditions were applied on all solid boundaries, which means that incoming boundary populations are equal to out-going populations after the collision. A comparison with other study is done and a good result is gained. The results show that the Knudsen number has important role in heat transfer and the highest mean temperature at outlet occurs at highest Knudsen number and heat transfer convection is more significant for first heat source comparing second heat source. Highlights: Four heat sources are located in the upper and lower walls. Lattice Boltzmann method is used to solve related equations of flow and temperature. Average temperature in micro channel increased by increasing Knudsen number.